Potret Perkembangan Metodologi Kelompok Orientalis dalam Studi Al-Qur’an - Ihwan Agustono (Universitas Darussalam Gontor, 2020)
Qur’anic studies in the Western countries has a long history. Started with the defeat experienced by Christians in the Crusades, Western scholars began to start their interaction with the Holy Qur’an in order to find out more about the teaching of Islam. In the span of nearly ten centuries, the Orientalists had introduced various models of approaches, characteristics of thought to various controversial accusations that were baseless related to the Holy Qur'an. If it was examined more deeply, it would be clear that among Western scholars themselves also occur unending dialectic. These dialectics, either in the form of support and criticism, caused the study of the Qur’an in the Western Scholarship seemed more alive and dynamic. In this paper, the writer tries to describe the development of the Qur’anic studies in the West, especially those conducted by the non-Muslim Western scholars. The development will be formulated in the form periodic of the long history of the study of the Qur’an in the West. It was beginning from the era of the translation of the Qur'an in the 12th century until the contemporary era of the Qur’anis studies, The methodology used in the study of the Qur’an was the emphasis in the history of the codification of the Qur’an, as an attempt to show the influence of culture in the verses of the Qur’an, and to undermine the authenticity of the Qur'an as the great revelation.